2018
DOI: 10.1590/0103-8478cr20170705
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of vitamin D3 and supplementation with 1,25-dihydroxyvitamin D3-glycoside on performance, carcass yield and bone quality in broilers

Abstract: An experiment was performed to evaluate the effect of decreased levels of vitamin D3 in the premix and 1,25-dyhydroxyvitamin D3-glycoside (1,25(OH)2D3-glycoside) supplementation on performance, carcass yield and bone quality in 42d old broilers. Seven-d-old male chickens Cobb500® were distributed in a randomized design with six treatments: a control diet with inclusion of vitamin D3 in the premix, without supplementation of 1,25(OH)2D3-glycoside, and five diets with decreased levels of vitamin D3 (100%, 75%, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Research, Society and Development, v.9, n.7, e119973975, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.3975 Alves et al (2018) e Alves et al (2019) constataram menor CR e GP, e consequente pior CA, em frangos de corte aos 42 dias de idade, quando o 1,25(OH)2D3 foi fornecido como fonte exclusiva da vitamina D. Segundo os autores, o metabólito, como fonte única da vitamina D não se constituiu em vantagem zootécnica. Tal justificativa, corroborou com os achados do presente estudo e contribuiu para a validação da estratégia nutricional pesquisada, ou seja, produtividade não afetada com níveis de vitamina D3 mantidos e adição de 1,25(OH)2D3.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Research, Society and Development, v.9, n.7, e119973975, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.3975 Alves et al (2018) e Alves et al (2019) constataram menor CR e GP, e consequente pior CA, em frangos de corte aos 42 dias de idade, quando o 1,25(OH)2D3 foi fornecido como fonte exclusiva da vitamina D. Segundo os autores, o metabólito, como fonte única da vitamina D não se constituiu em vantagem zootécnica. Tal justificativa, corroborou com os achados do presente estudo e contribuiu para a validação da estratégia nutricional pesquisada, ou seja, produtividade não afetada com níveis de vitamina D3 mantidos e adição de 1,25(OH)2D3.…”
Section: Resultsunclassified
“…O 1,25(OH)2D3 tem como principal receptor as células da mucosa intestinal, responsáveis pela absorção de Ca; relaciona-se com a expressão de um RNA mensageiro específico, e a subsequente síntese de proteína transportadora de Ca, a calbindina (Figueiredo Jr. et al, 2018;Vieites et al, 2018). Nos últimos anos, o uso do 1,25(OH)2D3 nas rações para frangos de corte vem sendo estudado (Souza et al, 2013;Vieites et al, 2017Vieites et al, , 2018Castro et al, 2018;Alves et al, 2018;Alves et al, 2019). De modo geral, os resultados verificados pelos pesquisadores indicaram que a utilização do metabólito não comprometeu as variáveis produtivas e ósseas das aves.…”
Section: Introductionunclassified
“…In addition to, stated that in starter period, there were no significant differences between vitamin D3 dietary treatments for FC. Alves et al (2018) found that the performance variables FC during the 7 -42 days period were significantly poor (P<0.05) when the metabolite 1, 25(OH)2D3-glycoside was used as the single source of vitamin D. Lin et al (2002) and MendonçaJúnior et al (2002), did not verify any differences on FC of hens supplied with VIT A supplementation. On the contrary, Frost and Roland (1990) determined a significant 3 g/h/d improvement of FC when hens were fed a diet supplemented with 1,500 IU/kg of D3 and 1 μg/kg of 1,25-(OH)2-D3 with0.55% P and 3.75% Ca.…”
Section: Feed Consumption (Fc)mentioning
confidence: 92%
“…D3, Bajwa et al (2020) explained that supplementation of vitamin D sources improved the growth performance (P<0.05). On the other side, Alves et al (2018) found that the performance variables BW at ages from 7 to 42 days were significantly poor (P<0.05) when the metabolite 1, 25(OH) 2D3glycoside was used as the single source of vitamin D. Edwards et al (1994) reported that birds fed no VITD3 were exposed to ultraviolet light from battery fluorescence tubes required 800 to 1,600 IU/kg of dietary VITD3 to provide maximum response for 16-d body weight,. Also, Han et al (2009) reported that supplementation of 5 μg 1 -α(OH)D3/kg to broiler chicken diet containing 5 μg cholecalciferol/kg had negative effects on BW of broiler chickens, which indicated that 1 -α(OH)D3, could not enhance growth performance indices of broiler chickens when basal diet contained adequate content of cholecalciferol…”
Section: Body Weightmentioning
confidence: 99%
“…No presente estudo, os frangos que receberam o 1,25(OH) 2 D 3 como fonte única de vitamina D, consumiram a menor quantidade de ração, também apresentando as piores médias de peso e de ganho de peso, este fato demonstra que o fornecimento do metabólito, como fonte única da vitamina não se constituiu em vantagem zootécnica. Resultados semelhantes foram observados por Brito et al (2010), que utilizando um metabólito de vitamina D3, o 25(OH)D 3 ), observaram menor consumo de ração quando esse metabólito foi fornecido como única fonte de vitamina D no suplemento, assim como, Alves et al (2018) que também verificaram menor consumo de ração e ganho de peso, gerando uma pior conversão alimentar de frangos de corte aos 42 dias quando o 1,25(OH) 2 D 3 foi fornecido como fonte exclusiva de vitamina D. Castro et al (2018), não observaram diferenças no desempenho de frangos de corte aos 21 e 42 dias de idade quando, incluíram a mesmo metabólito da vitamina D utilizado no presente estudo, acompanhado de redução ou não de 50% da vitamina D3 no suplemento vitamínico.…”
Section: Ingredientes (%)unclassified